Nasal washes in chronic rhinosinusitis, review article (International Journal of Medical and Surgical Sciences, 2023)
Chronic rhinosinusitis (CRS) is a chronic condition of inflammation in the mucosa of the paranasal sinuses that is associated with a significantly impaired quality of life, which motivates the constant study of therapies for its control and cost reduction. The cutting edge of clinical management for CRS is topical therapy. The advantages of topical medical therapy include direct administration of the drug into the diseased tissue, the possibility of administering higher local concentrations of the drug and minimizing systemic absorption which is not without adverse effects, thus becoming an important strategy in the management of CRS. The objective of this literature review is to formally review and identify topical medical therapy strategies and promote an evidence-based approach to their use. A literature review was conducted based on a keyword search. The computerized databases of PubMed, ElSevier and ResearchGate were accessed. We included articles highlighting the results of the use of topical therapies in CRS and that the type of study was a clinical trial. This review identified and evaluated the literature on topical therapy strategies for CRS: saline irrigation, topical antibiotics, topical steroids, and topical antifungals. Topical therapy has become an important tool in the treatment arsenal for CRS. Based on a review of the literature, nasal irrigation with saline and topical steroid sprays are the most evidence supportive. Nonstandard topical nasosinusal steroid therapies may be an option for managing CRS.
Keywords: Rhinosinusitis; nasal washes; topical therapy